1970
DOI: 10.3329/ujzru.v28i0.5282
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Productive and Reproductive Performances of Red Chittagong Cow at rural areas in Chittagong

Abstract: The result of the collected data revealed different reproductive performances of RedChittagong Cow such as age at puberty 2.68±1.72 years, days required to first heat during postpartum period 3.08±1.00 months, calving interval 14.00±1.19 months, service per conception1.36±0.60 and gestation length 279.92±5.27 days. In this survey some data were recorded toobserve the production performances of Red Chittagong Cows. Milk production per day andlactation length was 2.10±0.63 liter and 238.8±30.6 days, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
5
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
7
5
3
Order By: Relevance
“…Habib (2011) found 1.4 ± 0.1 for the same herds. The result is similar to the reports (1.2 to 1.4 ± 0.1) reviewed by Azizunnesa et al (2010); Das et al (2010); Habib et al (2003) for the same genotype in different herds. Higher range (1.5 4 ± 0.1 to 1.6 ± 0.6) was reported by Hossain et al (2006); Bag et al (2010) in the same genotype in different herds.…”
Section: Number Of Services Per Pregnancy (Nsp)supporting
confidence: 82%
“…Habib (2011) found 1.4 ± 0.1 for the same herds. The result is similar to the reports (1.2 to 1.4 ± 0.1) reviewed by Azizunnesa et al (2010); Das et al (2010); Habib et al (2003) for the same genotype in different herds. Higher range (1.5 4 ± 0.1 to 1.6 ± 0.6) was reported by Hossain et al (2006); Bag et al (2010) in the same genotype in different herds.…”
Section: Number Of Services Per Pregnancy (Nsp)supporting
confidence: 82%
“…The average age at first service of RCC was 2.7±1.7 years (Table 6) which was very much close with the findings of Azizunnesa et al (2010) as 32.2 months, Bag et al (20100) as 32.42 months and Ashraf (1998) as 2.6 years for indigenous cattle and was lower than the findings Ali (1994) as 3.5 years and Kamal (2010) as 1216±121.6 days.…”
Section: Age At First Servicesupporting
confidence: 83%
“…Khan et al (2000) also reported the closer lower values of daily milk yield both in farm (2.0±0.63) and in rural condition (1.8±0.9). The average lactation length of RCC cow was 243.1±25.2 days (Table 4) which was higher than the reports of Bag et al (2010) as 210.12±7.59 days, Azizunnesa et al (2010) as 238.8 days and Khan et al (2000) reported as 214.7 ± 21.8 days. Mufti et al (2009) reported the closer values of lactation length of RCC at farm condition (230.6±23.9 days) whereas Habib et al (2003) and also reported a higher lactation length of RCC at farm condition (261.1±14 days) and 259.6±6.2 days respectively.…”
Section: Cultivation Of Crops/paddycontrasting
confidence: 52%
“…The result of this study agrees with the range reported by the Azizunnesa et al (2010) for RCC (14.0 to 14.84 months, i.e 420 to 445 days). Calving interval may vary due to the effect of genetic, nutritional, environmental and managemental condition.…”
Section: Calving Intervalsupporting
confidence: 83%
“…Calving interval, age at puberty, service per conception, gestation length and birth weight of fetus are most important parameters to measure the farm economy. A farm with 13-15 months calving interval, 24 months for age at puberty, 1.33 services per conception and 5 kg milk per day per cow could be economically profitable (Azizunnesa, 2010). Milk availability per capita is approximately 125.59 ml per day per head in Bangladesh, against the FAO recommendation of 250 ml per day per head as the standard (DLS, 2015-16).…”
Section: Introductionmentioning
confidence: 99%